2022
DOI: 10.3389/fclim.2022.1016164
|View full text |Cite
|
Sign up to set email alerts
|

Community-based approaches to support the anchoring of climate-smart agriculture in Tanzania

Abstract: We assess the impact of community-based approaches to promote adoption of integrated climate smart agriculture (CSA) practices based on soybean cultivation combined with mulching, intercropping, crop rotation, manure application and rhizobium inoculation methods. We use quasi-experimental data of farmers participating in Farmer Field Business Schools (FFBS) and Village Savings and Loan Associations (VSLAs) in Iringa region of Tanzania. Farmers received technical training and financial support for the initial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Topic two constitutes the importance of the gender approach in the study of CSGs, since the word "woman" has the highest Beta value in the graph. Several works found that CSGs empower women (Karlan et al, 2017;Pamuk et al, 2022). The CSGs constitute a mechanism that trains women on various topics.…”
Section: Sustainability and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Topic two constitutes the importance of the gender approach in the study of CSGs, since the word "woman" has the highest Beta value in the graph. Several works found that CSGs empower women (Karlan et al, 2017;Pamuk et al, 2022). The CSGs constitute a mechanism that trains women on various topics.…”
Section: Sustainability and Performancementioning
confidence: 99%
“…The fifth topic is the participation and impact of the CSG in the agricultural sector and it is taken into consideration because the projects are usually implemented in predominantly agricultural territories. Pamuk et al (2022) concluded that CSGs positively affect the adoption of climate-smart agriculture practices. Amponsah et al (2023) found that participation in CSGs significantly increased the agricultural productivity and income of the participants.…”
Section: Sustainability and Performancementioning
confidence: 99%
“…The CSV approach-including its savings and credit component-builds on local social capital, through the CBOs and their member groups, with a high degree of women membership, and the potential to reach poorer farmers. For example, Pamuk et al (2022) estimated a positive effect on the adoption rates of several CSA practices for farmers receiving microfinance services (and trainings) from CBOs, and this effect became more pronounced for households with higher scores on women empowerment. As the inclusion of CBOs is a key element in intervention models that promote the inclusiveness of agricultural innovations (Hoffecker 2021;Pamuk et al 2022), we could expect a positive effect on the distributional patterns of CSA adoption.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Pamuk et al (2022) estimated a positive effect on the adoption rates of several CSA practices for farmers receiving microfinance services (and trainings) from CBOs, and this effect became more pronounced for households with higher scores on women empowerment. As the inclusion of CBOs is a key element in intervention models that promote the inclusiveness of agricultural innovations (Hoffecker 2021;Pamuk et al 2022), we could expect a positive effect on the distributional patterns of CSA adoption. However, the previous literature has paid little attention to the distributional impact of the CSV approach and improved access to savings and credit.…”
Section: Introductionmentioning
confidence: 99%
“…Groups usually have 30-50 members and are governed by a strict set of rules, either written or unwritten, depending on the group's literacy. Breaching the rules is considered "taboo" and comes with social repercussions and possible financial penalties or ostracism" [12,[13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%